2019
DOI: 10.1038/s41385-019-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory cytokine function in the respiratory tract

Abstract: The respiratory tract is an important site of immune regulation; required to allow protective immunity against pathogens, while minimizing tissue damage and avoiding aberrant inflammatory responses to inhaled allergens. Several cell types work in concert to control pulmonary immune responses and maintain tolerance in the respiratory tract, including regulatory and effector T cells, airway and interstitial macrophages, dendritic cells and the airway epithelium. The cytokines transforming growth factor β, interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
83
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 172 publications
(212 reference statements)
4
83
0
3
Order By: Relevance
“…Pulmonary immunity must be tightly regulated by anti-inflammatory cytokines to minimize tissue damage that might compromise respiratory function. 18 Asthma is thought to occur because of an imbalance between immune activation and regulation in the respiratory tract, prompting efforts to boost regulatory mechanisms by immunotherapy to treat allergic diseases. 54 The cytokine IL-10 can regulate diverse T H cell responses to limit immunopathology, 11 including T2 immunity in murine models of asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary immunity must be tightly regulated by anti-inflammatory cytokines to minimize tissue damage that might compromise respiratory function. 18 Asthma is thought to occur because of an imbalance between immune activation and regulation in the respiratory tract, prompting efforts to boost regulatory mechanisms by immunotherapy to treat allergic diseases. 54 The cytokine IL-10 can regulate diverse T H cell responses to limit immunopathology, 11 including T2 immunity in murine models of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…11,16,17 Therefore IL-10 can act through diverse mechanisms to limit pulmonary immunopathology in different contexts. 18 T H cell-derived IL-10 is a key mediator of induced tolerance to allergens 19,20 and resolution of allergic inflammation. 21 Conversely, impaired IL-10 production by T H cells has been reported in patients with severe asthma, 22,23 and genetic variants affecting IL-10 expression have been associated with asthma incidence and severity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to marathons, our group previously demonstrated that marathon runners who had increased IL-10 levels in the circulation immediately after the marathon and also in the nasal mucosa 72 hours after the marathon did not present upper respiratory symptoms [12,33]. In addition, it has been also reported that systemic IL-10 can modulate the pulmonary function by modulating the inflammatory response of the airways [29,45], including that associated with physical exercise [50,51]. However, studies that aimed to evaluate the effect of IL-10 in the context of EIB are scarce [52,53].…”
Section: Discussionmentioning
confidence: 93%
“…Cytokines are proteins that present many functions, such as the regulation of inflammatory responses, chemotaxis, and cell activation, among others [28,29]. During physical exercise, muscle contractions elicit the release of several molecules, including cytokines such as IL-1ra, IL-6, IL-8, IL-10, and TNF-α [30,31].…”
Section: Discussionmentioning
confidence: 99%